An Analysis of Presupposition in International News Reporting on Environmental Disaster in Sumatra - Zalfa Zahira; Bunyamin Faisal; Erfan Muhammad Fauzi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines how presuppositions construct narratives in international media coverage of recent environmental disasters in Sumatra, specifically focusing on the flash floods and landslides that occurred in late 2024. Using a qualitative descriptive method, the study analyzes eight news articles from four international outlets: BBC, The Guardian, France 24, and Al Arabiya. The analysis applies Yule’s (1996) grammatical presupposition framework and Levinson’s (1983) sub-classifications. These grammatical triggers are then cross-tabulated with emerging thematic categories, such as Ecology, State/Politics, and Physical Damage. From 261 identified triggers, Lexical Presuppositions dominate the dataset at 68.2%, primarily conveyed through verbs of change and comparison. The cross-tabulation reveals strategic framing across themes. Lexical verbs of state change establish human causality within ecological frames. Meanwhile, structural negation presupposes state administrative failure, whereas factive presuppositions validate the state's official narrative. Ultimately, presuppositions function as architects of implicit reality in news discourse. They allow the media to naturalize subjective interpretations, presenting them as objective facts to readers.